Penetapan Upah Minimum di Masa Pandemi Covid-19 Pada Kabupaten Serang Banten Pasca Terbitnya Surat Edaran Menteri Ketenagakerjaan Republik Indonesia tentang Penetapan Upah Minimum Tahun 2021 - Dhiba Farras Ety (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
The sharp polemic that erupted between workers and employers in Serang Regency over the Determination of the Serang Regency Minimum Wage was over whether the Serang Regency Minimum Wage should be reviewed from the perspective of the PP's No. 78 of 2015 concerning Wages or from the perspective of the Minister of Manpower of the Republic of Indonesia's Circular Letter M/11/HK.04/X/2020 concerning the Determination of Minimum Wage in 202. The purpose of this study is to ascertain the nature of the disagreements between the parties involved in determining the Minimum Wage in Serang Regency following the issuance of the Circular Letter of the Minister of Manpower of the Republic of Indonesia Number M/11/HK.04/X/2020 concerning the Determination of the Minimum Wage in 2021 During the 2019 Coronavirus Disease Pandemic (Covid-19), such that it is deemed unenforceable and in violation of the PP. No. 78 of 2015 concerning The premise of this research is to ascertain the legal consequences of implementing the Circular Letter of the Minister of Manpower of the Republic of Indonesia, No: M/11/HK.04/X/2020 concerning Minimum Wage Determination in 2021 During the Covid-19 Pandemic, if it conflicts with the PP. No. 78 of 2015 concerning Wages in determining the Minimum Wage in Serang Regency. This is a normative or empirical study with a qualitative approach. This study makes use of the Legal Justice and Legal Assurance Theories. Minimum Wage Determination Based on Circular Letter M/11/HK.04/X/2020 of the Minister of Manpower of the Republic of Indonesia Concerning Minimum Wage Determination in 2021 During the Pandemic Coronavirus Disease 2019 (Covid-19) has binding legal force if the Circular Letter's points are followed. This becomes a clause in a collective bargaining agreement/agreement between the entrepreneur and the worker/laborer.Keywords: Minimum Wage Determination; Pandemic Coronavirus Disease 2019 (Covid-19); Legal Justice Theory; Legal Assurance Theory. AbstrakPolemik tajam yang terjadi antara pihak pekerja dan pihak pengusaha di Kabupaten Serang mengenai Penetapan Upah Minimum Kabupaten Serang adalah: dari sudut pandang mana Penetapan Upah Minimum Kabupaten Serang tersebut ditinjau, apakah dari sudut pandang PP. No 78 Tahun 2015 Tentang Pengupahan atau dari sudut pandang Surat Edaran Menteri Ketenagakerjaan RI, Nomor: M/11/HK.04/X/2020 Tentang Penetapan Upah Minimum Tahun 2021 Pada Masa Pandemi Coronavirus Disease 2019 (Covid-19)? Penelitian ini bertujuan untuk mengetahui Pertentangan apa yang menjadi ketidaksepakatan para pihak dalam penetapan Upah Minimum di Kabupaten Serang dengan dikeluarkannya Surat Edaran Menteri Ketenagakerjaan RI, No: M/11/HK.04/X/2020 Tentang Penetapan Upah Minimum Tahun 2021 Pada Masa Pandemi Coronavirus Disease 2019 (Covid-19) sehingga dianggap tidak dapat dilaksanakan dan bertentangan dengan PP. No 78 Tahun 2015 Tentang Pengupahan. Adapun pemikiran yang melandasi penelitian ini adalah untuk mengetahui akibat hukum dari implementasi Surat Edaran Menteri Ketenagakerjaan RI, No: M/11/HK.04/X/2020 Tentang Penetapan Upah Minimum Tahun 2021 Pada Masa Pandemi Covid-19 apabila bertentangan dengan PP. No 78 Tahun 2015 Tentang Pengupahan dalam penetapan Upah Minimum di Kabupaten Serang. Penelitian ini adalah penelitian normatif atau empiris, dengan bentuk kualitatif. Penelitian ini menggunakan Teori Keadilan Hukum dan Teori Kepastian Hukum. Penetapan Upah Minimum berdasarkan Surat Edaran Menteri Ketenagakerjaan RI Nomor : M/11/HK.04/X/2020 Tentang Penetapan Upah Minimum Tahun 2021 Pada Masa Pandemi Coronavirus Disease 2019 (Covid-19) memiliki kekuatan hukum mengikat apabila point-point dari Surat Edaran tersebut menjadi suatu klausa dalam suatu perjanjian/kesepakatan bersama antara pekerja/buruh dan pengusaha. Kata Kunci: Penetapan Upah Minimum, Pandemi Coronavirus Disease 2019 (Covid-19), Teori Keadilan Hukum, dan Teori Kepastian Hukum.